Factors impeding withdrawal from a violent relationship: variations based on integration and social exclusión - Damonti, Paola; Amigot Leache, Patricia (Cuadernos de Trabajo Social, 2021)
This article analyses processes involved in ending a relationship with a partner in cases of gender-based violence. It specifically examines how the factors that impede withdrawal from a violent partner can vary based on the situation of integration and social exclusion in which women find themselves. This is a topic that has not been the subject of published research. To conduct the study, we performed 16 in-depth interviews with women who are survivors of this form of violence. The women interviewed reported that material factors (such as lack of own financial resources or viable residential alternatives, absence of social support, insufficient or inadequate benefits and an unfavourable economic context) tended to be particularly significant in situations of exclusion. To the contrary, symbolic and subjective factors (great importance of partner in terms of personal and social identity, fear of loneliness, emotional dependence, fear of failure and shame from other people becoming aware of the situation) appear to be more significant in the context of integration than exclusion, particularly among middle- and upper-class women. These findings may prove highly useful in designing social policies and for social intervention, since they facilitate a case-by-case assessment of the factors that presumably carry most weight in terms of women remaining in violent relationships, and therefore offer the possibility of adjusting professional actions to their context.